The Committee : A Study of Policy, Power, Politics and Obama's Historic Legislative Agenda on Capitol Hill - Marshall, Bryan W.; Wolpe, Bruce C., 1951- (Book collections on Project MUSE., 2018)
For three years while serving as a senior adviser to Rep. Henry A. Waxman (D-CA), chairman of the House Committee on Energy and Commerce-one of the most powerful committees in Congress-Bruce C. Wolpe kept a diary, a senior staffer's look at how committees develop and promote legislation. With its insider's view of the rough-and-tumble politics of cap-and-trade, healthcare reform, tobacco, oversight, and the debt ceiling agreement, The Committee uniquely melds the art of politics and policymaking with the theory and literature of political science. The authors engage with the important questions that political science asks about committee power, partisanship, and the strategies used to build winning policy coalitions both in the Committee and on the floor of the House. The insider politics and strategies about moving legislation in Congress, from internal and external coalition building to a chairman's role in framing policy narratives, will captivate both novice and die-hard readers of politics.